Multimedia Interaktif Pengenalan Tatacara Sholat Berbasis Animasi 3D Untuk Siswa Tingkat Sekolah Dasar - Sahputra, Eka; Reswan, Yuza; Baihaqi, Ikhwan (UNIVED Press, 2020)
Life cannot be separated from the relationship between humans and God, one way is prayer as the 2nd pillar of Islam. Prayer is something that is mandatory for every Muslim starting from puberty and sanity. Due to foreign influences that have deeply entered into children's cultural thinking, material about prayer is highly recommended in the era of globalization. The current problem is that the media used is still conventional. Students can only listen to explanations from the teacher. This sometimes makes students feel bored and lazy to learn because there is no interaction that gives students an active role. This learning media uses picture learning books (which are used as markers to be saved by the smartphone, becoming 3-dimensional, 3D animation).